Role and influence of Agriculture in Indian economy. - sharma, Geetu (Universal Research Reports, 2017)
Agriculture is the cornerstone for the rural Indian economy which revolves on socio-economic advantages and privileges, and any change in its structure may have a commensurate effect on current social equality patterns. Sustainable Agricultural production relies on proper usage under an appropriate technological management within the existing socioeconomic infrastructure of natural resources (soil, water, animal and plant genetic engineering, fishing, forestry, climate, precipitation and topographing). Various research studies and policy papers emphasise the resource restrictions, infrastructural constraints, institutional constraints, technological limits and policy constraints facing the Indian Agriculture Sector. In order to accomplish sustainable agriculture, natural resources, financial resources, institutional resources and human resources must be combined (i.e. to optimally utilise the agricultural resources). As a feasible technology, IT plays a significant role in fast economic development and social change in emerging nations. Information technology and bio-technology, which are "the driving forces" of globalisation, are likely to generate new risks and vulnerabilities for the Indian agricultural industry with their complementarities of liberalisation, privatisation and stricter IPR.